(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in the process of socialization of the family, it was tried to scientifically-theoretically study the socio-philosophical foundations of the formation and development of entrepreneurial knowledge and skills of young people. It was also stated that our country will go through the reforms carried out in the period of new development in the field of improving entrepreneurial skills in the family and improving the knowledge and professional skills of our citizens, especially young people in the field of entrepreneurship. As a result of the research carried out, a number of proposals and practical recommendations regarding the improvement of entrepreneurial skills in Family Promotion have been made.